Sensitivity and Specificity of Modified Early Obstetric Warning Score (MEOWS) and Maternal Early Warning Criteria (MEWC) for Maternal Morbidity: A Retrospective Cohort Study in Pregnant Women with COVID-19 - Cahyani, Dinda Desti; Priyanto, Heru; Dhiya An, Alfun; Supriyatiningsih (Indonesian Journal of Obstetrics and Gynecology, 2024)
Objective: To measure the comparative sensitivity, specificity, and predictive value of MEOWS and MEWC in predicting morbidity in pregnant patients infected with COVID-19. This research can be one of the screenings used to determine the level of care for pregnant patients with COVID-19. Methods: The retrospective cohort technique was used to examine the 89 pregnant women with COVID-19 who were admitted to the Bantul Regional General Hospital between January and December 2021. Data analysis used the ROC curve to compare sensitivity, specificity, and predictive value. Results: MEWC is better than MEOWS in predicting the morbidity of pregnant patients with COVID-19 infection. This is because MEWC has a better sensitivity (78,3%) and PPV value (78%) than MEOWS, even though it has a lower specificity value (81,8%) and NPV value (82%). The specificity value of MEWC (81.8%), when compared to MEOWS (97.1%), does have a lower specificity value. The results of MEOWS and MEWC data analysis using ROC produce an area under the curve for MEOWS of 74,9% while for MEWC of 80%. Discussion: MEWC has a better sensitivity indicating that patients who do not trigger MEWC criteria will have a low risk of experiencing maternal morbidity. Screening tools will prioritize the sensitivity value compared to the specificity value of the instrument used. A screening tool will have a lower positive predictive value if the study population has a lower prevalence of morbidity. Based on the comparison of the predictive value, sensitivity, and specificity of the MEWC and MEOWS instruments, it can be concluded that MEWC is associated with maternal morbidity with a higher sensitivity than MEOWS, although it has a lower specificity. High sensitivity values will result in screening tools with consistent results. The ROC curve can also show that MEWC has a higher sensitivity value by looking at the Y-coordinate, which is higher than the Y-coordinate of MEOWS. MEWC has a better Receiver Operator Curve (ROC) intersection point than MEOWS, where the MEWC intersection point has the furthest point on the upper left of the ROC diagonal line. Conclusion: MEWC has a higher sensitivity compared to MEOWS, even though it has a lower specificity. High sensitivity values will produce screening tools with consistent results. Keywords: MEWC, maternal early warning system, maternal morbidity, MEOWS